Species distribution modelling of invasive alien species; Pterois miles for current distribution and future suitable habitats - C. Turan (Global Journal of Environmental Science and Management)
The present study aims to predict the potential geographic distribution and future expansion of invasive alien lionfish (Pterois miles) with ecological niche modelling along the Mediterranean Sea. The primary data consisted of occurrence points of P. miles in the Mediterranean and marine climatic data layers were collected from global databases. All the used models run 100% success predictions, and true skill statistics and area under the receiver operating characteristic curve values ranged from 0.42 and 0.71 to 0.86 and 0.95 for current distribution modelling; and 0.0 and 0.0 to 0.83 and 0.94 for the future distribution modelling, respectively. The mean sea surface temperature and maximum bathymetry played an important role in the prediction of the model and explained relatively higher biological importance to the extension and adaptation of P. miles with extreme environmental factors. The predicted suitable habitats of P. miles under the current climate dominantly occurred in the east parts of coastal areas of the Mediterranean. The predicted future suitable habitats of P. miles revealed that P. miles increase its range of distribution dominantly to the central and west part of the Mediterranean in a spatial extent, indicating high suitability of these areas for its future distribution.